1997
DOI: 10.1007/s003920050065
|View full text |Cite
|
Sign up to set email alerts
|

Intraventrikuläre Obstruktionen bei der Dobutamin-Streßechokardiographie: Determinanten ihrer Entstehung und klinische Folgen (Dynamic intraventricular obstruction during dobutamine stress echocardiography. Determinants of the phenomenon and clinical consequences)

Abstract: Intraventricular obstructions during DSE are often observed in pts with normal systolic function at rest and during peak stress, especially in the case of left ventricular hypertrophy. (ABSTRACT TRU

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Therefore, the development of a mild to moderate intraventricular gradient during dobutamine stress is frequent and may have no major clinical significance in the majority of patients with LVBS as in the general population. The significant association found in our patients between dynamic intraventricular gradient and septal hypertrophy is in keeping with the studies by Khanal et al [21] and Wagner et al [9], who showed that dobutamine-induced LV cavity obliteration was associated with female sex and LV hypertrophy. Thus, the dynamic intraventricular obstruction documented in our patients does not seem to be a specific feature of LVBS, but rather depends upon the presence of a localized septal hypertrophy that is frequently found in elderly women.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the development of a mild to moderate intraventricular gradient during dobutamine stress is frequent and may have no major clinical significance in the majority of patients with LVBS as in the general population. The significant association found in our patients between dynamic intraventricular gradient and septal hypertrophy is in keeping with the studies by Khanal et al [21] and Wagner et al [9], who showed that dobutamine-induced LV cavity obliteration was associated with female sex and LV hypertrophy. Thus, the dynamic intraventricular obstruction documented in our patients does not seem to be a specific feature of LVBS, but rather depends upon the presence of a localized septal hypertrophy that is frequently found in elderly women.…”
Section: Discussionsupporting
confidence: 93%
“…These findings and the association of dobutamine-induced dynamic intraventricular gradient with worsening of apical wall motion recently reported in 2 patients with LVBS and septal hypertrophy [7] suggested a possible pathogenetic role for dynamic intraventricular obstruction in LVBS. The prevalence of dobutamine-induced dynamic obstruction in our patients with LVBS is similar to that reported by previous studies in patients undergoing dobutamine stress echocardiography for evaluation of coronary artery disease [8-11,20-22], that showed a prevalence ranging from 13% in the study by Heinle et al [10] to 53% by Wagner et al [9]. Therefore, the development of a mild to moderate intraventricular gradient during dobutamine stress is frequent and may have no major clinical significance in the majority of patients with LVBS as in the general population.…”
Section: Discussionsupporting
confidence: 90%